Reclaiming a plundered past : archaeology and nation building in modern Iraq - Bernhardsson, Magnus Thorkell (University of Texas Press, 2005)
The looting of the Iraqi National Museum in 2003 provoked a world outcry at the scale of the losses but as this work shows, it was hardly the first time. Since Iraq was created in 1921, the modern state has used archaeology to forge a sense of nationhood and political legitimacy.